An attitude of ego psychology towards development and mental disorders of adolescents - Kalpokienė, Vaida (Psichologija, 2005)
Period of adolescence is specific because a very rapid development is going but there is also a period when serious mental disorders begin – schizophrenia, depression, personality disorders, etc. Although many psychological theories study the reasons of psychopathology manifestation in adolescence, yet psychodynamic paradigm which emphasizes a meaning of internal processes towards personality functioning may help to answer a question what are the underlying reasons which encourage the beginning of one or another dysfunction. One of the reasons may be a disturbance of Ego functioning. Hartmann (1964) asserts that Ego is responsible for an adaptation and mental health, its development is very rapid during adolescence (Blos, 1962), so two questions are analysed in this article: normal Ego development and disturbances of Ego functioning during adolescence. We are trying to answer these questions both reviewing classical attitude towards Ego development during adolescence (with reference of S. Freud, A. Freud, H. Hartmann, E. Erikson, P. Blos works) and analyzing empirical researches of late years. P. Blos (1962) gives nearly the most consistent attitude towards developmental processes running during adolescence. By his opinion, the process of individuation-separation repeats itself during adolescence, i.e. adolescent seeks to separate from his/her parents and to create his/her own feeling of identity. Oscillation of regress and progress is typical characteristic of Ego development, but psychopathology shows off when regress of Ego towards early developmental fixations is very pronounced and subsequent development comes to a dead lock (Blos, 1967). Current researches of adolescents’ Ego can be divided into three big groups: normal Ego development is investigated on J. Loevinger’s (1977) Ego development theory basis, where she distinguishes several separates stages of Ego development based on both the theoretical concepts of psychodynamic paradigm and ideas of other psychology trends (for example, humanistic psychology). The second group of researches analyses the development of identity feeling during adolescence based on theory of E. Erikson. Results of researches demonstrate that development of identity feeling goes on both during early adolescence and after adolescence is over and different aspects of identity feeling develop during different developmental periods. The third group of researches includes Ego function researches of separate mental disorders cases. Probably mostly investigatable are adolescents with borderline personality and behavioural disorders. It is established that disturbance of Ego functions is unequal in cases of different mental disorders, besides disturbance of Ego functions is related to disturbance of identity feeling, for example there is a very close relation between disturbance of identity feeling and disturbance of thought processes. If psychodynamic paradigm gives us some insights about the significance of Ego on mental disorders manifestation during adolescence but still there is a lack of empirical researches which might more clearly define development of separate Ego functions during adolescence, relation between Ego and identity feeling, the disturbance of Ego functioning in cases of mental disorders, etc.